Simulation of mold deformation and pattern interaction in nanoimprint lithography. Issue 1626 (8th April 2014) - Cleveland, Nicolas; Sun, Hongwei
Abstract: As an emerging manufacturing technique, nanoimprint lithography (NIL) can fabricate micro and nanoscale features of microfluidic devices at very high accuracy and reliability. In high-temperature TNIL process, a polymer melt such as polymethyl-methacrylate (PMMA) is heated beyond the melting temperature so that it behaves predominantly as a fluid during the imprint process. The process parameters such as pressure, temperature, and material properties play critical roles in the NIL process. In this work, the process of thermal nanoimprint lithography (TNIL) is studied computationally with emphasis on the effect of soft-mold deformation on polymer melt flow and finished result by-way-of fluid-structure interaction (FSI) technology. Process is assumed isothermal at 180 °C. Applications of this modeling technique range from micro- and nano-patterns used in micro-channels for biomedical devices to other applications such as biological/particle sensors or super-hydrophobic surfaces. The simulation result is compared to experimental results, and traits observed in TNIL done with soft mold are supported and explained through numerical results.